Directors’ duties of financially distressed companies in the time of COVID-19 - Aurelio GURREA-MARTINEZ, (Institutional Knowledge at Singapore Management University, 2020)
Unlike other jurisdictions around the world, several European countries require corporate directors to file for bankruptcy once a company becomes insolvent. For instance, under German law, corporate directors are required to file for bankruptcy within three weeks since they know, or ought to have known, that the company became insolvent on a balance-sheet or a cash-flow basis. Failure to comply with this duty may expose the directors to both civil and criminal liability. In Spain, a similar duty is imposed. However, instead of exposing directors to criminal liability, they can be subject to other sanctions (including disqualification and liability for the company’s debts) and the bankruptcy petition has to take place within two months rather than three weeks. Such a duty can be extended, however, for four additional months if the directors notify the court the commencement of negotiations with the company’s creditors with the purpose of reaching an out-of-court agreement.